PENGARUH TEKNIK RELAKSASI BENSON TERHADAP KECEMASAN PASIEN PRE OPERASI DI RUANGAN BEDAH RS ISLAM IBNU SINA PAYAKUMBUH TAHUN 2024 - Damaiyanti, Siska; Izzati, Wisnatul; Pratama, Engla Rati; Oktavia, Rini (Jurnal Kesehatan Lentera 'Aisyiyah, 2024)
Surgery can cause anxiety, if not addressed, it can interfere with the operation process and the patient's healing. Many patients who are about to undergo surgery experience anxiety because they do not know and think about the impacts that will occur after surgery. A form of non-pharmacological therapy that can reduce anxiety levels by providing the Benson relaxation technique. Benson relaxation technique. The aim of this research is to see the effect of the Benson relaxation technique on the anxiety of patients who will undergo surgery in the operating room at Ibnu Sina Islamic Hospital Payakumbuh in 2024. Quasi-experimental design with a one group pretest and posttest design without control, to determine the effect of the Benson relaxation technique on patient anxiety who will undergo surgery in the surgical room at RSI Ibnu Sina Payakumbuh in 2024. The sample in this study was 41 people. The results of the research showed that 33 respondents (80.5%) experienced moderate anxiety levels before the Benson relaxation technique in pre-operative patients and 31 respondents (75.6%) experienced mild anxiety levels after the Benson relaxation technique. It was found that the influence of the Benson relaxation technique on pre- and surgical anxiety levels was 4.9 with ap value of 0.000. It is hoped that the director and nursing section of RSI Ibnusina Payakumbuh can use the results of this research as a guide in implementing operational standards in reducing the anxiety level of surgical patients. Keywords: Benson Relaxation Technique, anxiety, surgery